Fluorescent aerosol observation in the lower atmosphere with an integrated fluorescence-Mie lidar. (April 2019) - Li, Baowei; Chen, Siying; Zhang, Yinchao; Chen, He; Guo, Pan
Highlights: A fluorescence-Mie lidar for observing fluorescent aerosols was developed in Beijing. The spatio-temporal variability of fluorescent aerosols in the lower atmosphere was investigated. The LIF results was validated by backward trajectories and local pollutants emission data. The mean ratio of LIF-to-Mie is good correlated with PM2.5 concentration. Abstract: An integrated fluorescence-Mie lidar was built to observe fluorescent aerosol at the altitude below 1.5 km. It was constructed with the third harmonic of Nd:YAG laser (355 nm), a Newtonian telescope and two single-channel photomultiplier tubes. Based on the Mie scattering theory and laser-induced fluorescence (LIF) theory, the vertical distribution of fluorescent aerosol was retrieved by the LIF-to-Mie signal ratio. As a common factor, the geometric form factor of the system was cancelled out when dividing LIF signal by Mie signal, therefore the high-precision of the LIF-to-Mie signal ratio was obtained in the lower atmosphere. After continuous observations under different air quality conditions, the time-height indications of fluorescent aerosol were obtained. The fluorescence efficiency was preliminary estimated. By combining the backward trajectories analysis and the local emission data of SO2 and NO2, the time-height indications were analyzed for investigating the sources of fluorescent aerosol. The correlation between PM2.5 concentration and the mean value of LIF-to-Mie signal ratio was also studied. The good agreement between the results indicate that the above mentioned method can be employed to analyze the spatio-temporal distribution of fluorescent aerosol and has a great potential in meteorological application.